2022
DOI: 10.1021/acsnano.2c01912
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Dependent Copper–Diphenylalanine Assemblies with Tough Layered Structure and Enhanced Catalytic Performance

Abstract: Chiral regulation to prepare functional materials has aroused considerable interest in recent years. However, little is known on the effect of chirality of ligands in the metal–organic coordination assembly process. We report the self-assembly of diphenylalanine peptide (Phe-Phe, FF), the core fragment of Aβ protein, with metal copper ion (Cu2+) into metal–organic assemblies with chirality-encoded structures and properties. The chirality-dependent metal–dipeptide assembles with different morphologies and supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…[31] In recent years, the supramolecular assembly strategy has become one of the effective ways to design and synthesize novel chiral nanomaterials with special structures and excellent properties. [32][33][34][35][36][37] According to whether chiral units are involved in the supramolecular assembly process, the construction methods of supramolecular chiral assemblies can be roughly divided into the following types: (1) "chiral + chiral" means that only chiral units are used to form ordered supramolecular structure, always exhibiting novel chiral properties beyond a single chiral molecule; [40,41] (2) "chiral + achiral" means that achiral units and chiral units are co-assembled to induce achiral assembly units to show chiral signals in a chiral environment; (3) "achiral + achiral" means complete assembly by achiral units through spontaneous symmetry breakage, leading to exhibiting chirality through their own structural characteristics. [42] Usually, there are two typical amplification effects of chiral induction, namely "Sergeants-and-Soldiers Principle" and "Majority-Rules".…”
Section: Supramolecular Chemistry and Chiralitymentioning
confidence: 99%
See 2 more Smart Citations
“…[31] In recent years, the supramolecular assembly strategy has become one of the effective ways to design and synthesize novel chiral nanomaterials with special structures and excellent properties. [32][33][34][35][36][37] According to whether chiral units are involved in the supramolecular assembly process, the construction methods of supramolecular chiral assemblies can be roughly divided into the following types: (1) "chiral + chiral" means that only chiral units are used to form ordered supramolecular structure, always exhibiting novel chiral properties beyond a single chiral molecule; [40,41] (2) "chiral + achiral" means that achiral units and chiral units are co-assembled to induce achiral assembly units to show chiral signals in a chiral environment; (3) "achiral + achiral" means complete assembly by achiral units through spontaneous symmetry breakage, leading to exhibiting chirality through their own structural characteristics. [42] Usually, there are two typical amplification effects of chiral induction, namely "Sergeants-and-Soldiers Principle" and "Majority-Rules".…”
Section: Supramolecular Chemistry and Chiralitymentioning
confidence: 99%
“…[ 31 ] In recent years, the supramolecular assembly strategy has become one of the effective ways to design and synthesize novel chiral nanomaterials with special structures and excellent properties. [ 32–37 ]…”
Section: Introduction Of Chiralitymentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination of amino acid residues in peptide chains with metal ions is very common in living organisms, for example, in metalloproteins and metalloenzymes, which perform very important functions in nature, including the storage and transport of oxygen and the transfer and catalysis of electrons. Inspired by this, peptide-based coordination polymers (CPs), crystals, and porous metal–organic frameworks (MOFs) with specific properties have received a lot of attention from researchers in recent years . For example, Ma et al reported flexible peptide-based CPs, that is, Cu­(GT)·2H 2 O, whose crystal structure can be regulated by the breakage and reformation of coordinate bonds .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many chirality-related studies have been intensively carried out to investigate the origin of chirality and fabricate chiral functional materials. [4][5][6][7] Chirality information can be divided into different absorption (ground state) and emission (excited state) of left (L)and right (R)-handed circularly polarized light, respectively. 8 Accordingly, exploring circularly polarized luminescence (CPL) not only facilitates understanding of the nature of chirality in the excited state but also helps us to develop novel chiroptical materials.…”
mentioning
confidence: 99%